Functional analyses of putative brassinosteroid insensitive 1-associated receptor kinase 1 and putative ethylene transcriptional coactivator from Malaysian indica rice variety (Oryza sativa L.) MR219 - Khew, Choy Yuen (2013)
Phytohormones integrate metabolic and developmental signals in plants. Active BRI1-Associated Kinase I (BAK1) is required to interact with Brassinosteroid Insensitive 1 for brassinosteroid perception and signal transduction that regulate plant growth and development while ethylene transcriptional co-activator (ETC) acts on ethylene-responsive transcription factors, which positively control the expression of ethylene-responsive plant genes to elicit a response appropriate to the stimulus. The aim of this study is to annotate the functions of two putative phytohormonerelated transcripts, OsI-BAK1 and OsI-ETC from a Malaysian rice variety, MR219. Functional annotation of phytohormone-related genes, which are closely related to yield, may offer new solution to increase rice yield in the country. In the present study, the function of OsI-BAK1 and OsI-ETC were investigated using a transgenic approach through gene overexpression and RNAi silencing. In this study, one overexpression vector, pMDC32-BAK1 and two RNAi vectors, pANDA-BAK1 and pANDA-ETC were constructed. These vectors, together with an existing overexpression vector pMDC32-ETC were transformed into rice MR219 through Agrobacterium-mediated transformation, respectively. After plant transformation, the phenotypic and molecular changes on the transgenic rice plants were analyzed. The transgenic rice plants overexpressing OsI-BAK1 had corrugated and twisted leaves at the early stage of growth. Histological analysis of these leaves showed some differences in their cell arrangement in the vascular tissue compared to that of the untransformed plants. The bulliform cells which were enlarged and plugged deep into leaf epidermis in these leaves could have contributed to the abnormal morphology of the leaf blades. Silencing of OsI-BAK1 in rice plants produced about two folds higher number of undeveloped green and unfilled grains compared to untransformed plants. Histological analyses were conducted on the rice hull, culms and leaves in OsI-BAK1RNAi plants. The longitudinal section of rice hull from OsIBAK1RNAi plants showed that the embryo was either absent or retarded in its development. Taken together, OsI-BAK1 gene may play an important role in the developmental processes of seeds and leaf cell arrangement. Embryogenic calli transformed with the overexpression vector harboring OsI-ETC could not regenerate.The constitutive expression of OsI-ETC in rice might increase the production of ethylene and inhibit shoot regeneration. The transgenic plant containing a construct designed for RNAi silencing of OsI-ETC showed no obvious morphological difference compared to that of untransformed plant. As it is possible that this construct did not actually function and the plant may not have been RNA silenced to give obvious phenotypic changes. Functional analysis of OsI-BAK1 and OsI-ETC in this study has shed light on their biological functions in rice.